2018
DOI: 10.12693/aphyspola.133.306
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity Study of Carbon Nanoforms using a Comet Assay

Abstract: Carbon nanoforms due to their unique properties can be applied in many areas also in medicine. This article presents preliminary genotoxicity studies of electrospun carbon nanofibers (ECNF). This material, apart from its numerous applications, may also be a candidate for use in medical therapy and diagnostics. Polyacrylonitrile (PAN) nanofibers received in the electrospinning process were carbonized and thereafter subjected to oxidation treatment (ECNF-F). Both types of fibres were analyzed with regard to geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The latest research results presented in this paper expand on the knowledge about the influence of carbon nanofibers on both cell viability and, most importantly, on genotoxicity and prove that not only surface functionalization but also carbonization of samples at higher temperatures, i.e., above 1000 °C (we observed it at 1500 °C) has positive effects on the cellular response. Therefore, if, on the one hand, the presence of oxygen functional groups (as confirmed in our earlier publication [ 64 ]) and, on the other hand, the increase in the degree of crystallinity of the samples do not induce genotoxic activity, there must be another factor related to carbon nanofibers carbonized at 750 °C and 1000 °C that produces this effect. Another factor that distinguishes the eCNF750 and eCNF1000 samples from the eCNF1500, eCNF1750 and eCNF2000 samples is the absence of nitrogen as a residue of nitrile groups present in the PAN precursor in the samples carbonized at the temperatures of 1500 °C, 1750 °C and 2000 °C.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The latest research results presented in this paper expand on the knowledge about the influence of carbon nanofibers on both cell viability and, most importantly, on genotoxicity and prove that not only surface functionalization but also carbonization of samples at higher temperatures, i.e., above 1000 °C (we observed it at 1500 °C) has positive effects on the cellular response. Therefore, if, on the one hand, the presence of oxygen functional groups (as confirmed in our earlier publication [ 64 ]) and, on the other hand, the increase in the degree of crystallinity of the samples do not induce genotoxic activity, there must be another factor related to carbon nanofibers carbonized at 750 °C and 1000 °C that produces this effect. Another factor that distinguishes the eCNF750 and eCNF1000 samples from the eCNF1500, eCNF1750 and eCNF2000 samples is the absence of nitrogen as a residue of nitrile groups present in the PAN precursor in the samples carbonized at the temperatures of 1500 °C, 1750 °C and 2000 °C.…”
Section: Resultssupporting
confidence: 62%
“…In the case of the tested samples, the increase in crystallinity did not affect genotoxicity or cell viability. Our previous studies also indicated that carbon nanofibers obtained at 1000 °C cause DNA damage (studies performed on normal human skin fibroblasts from the cell line CCL 110) compared with the controls [ 64 ]. The main reason was the lack of chemical functionalization of the surface and the high hydrophobicity of this type of material.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon nanofibers were subjected to oxidation treatment in concentrated nitric acid (V) at 65 • C for 1 h (Figure 1b). Then samples were cooled down in the solution to room temperature, washed and dried in a dryer [38]. The obtained membranes are shown in Figure 2a,c-f.…”
Section: Fabrication Of Nanocomposite Membranesmentioning
confidence: 99%
“…Two-dimensional correlation spectroscopy indicates the participation of carbon nanostructures in interactions with cells [33]. The increase in the I1723/I1732 intensity ratio seems to be related to the structure of nanofibers that interact with cells in a different way [38].…”
Section: Pcl Matrix Crystallinitymentioning
confidence: 99%
“…Our earlier study has shown that this form of carbon also requires a specific treatment to remove toxic carbonaceous fractions that may appear in its structure and that can be responsible for its biological behavior [51]. To date, many works have been devoted to the biocompatibility of CNT and graphene, while much less works have been published on the biocompatibility of carbon nanofibers.…”
Section: Introductionmentioning
confidence: 99%